Pemanfaatan Pipa sebagai Alat Tanam dan Penabur Pupuk di Lahan Perkebunan Warga Toapaya Selatan: Studi Kasus Wilayah Agrikultur Lokal - Dwi Handayani; Januar Januar; M Khairul; Auliana Okta; Herry Kurniawan; Nurhazianti Nurhazianti; Novi Zurianti Ayu; Nur Selinda; Rara Cahya Aprilya; Nur Asma Riani Siregar (Sekolah Tinggi Ilmu Ekonomi Pariwisata Indonesia Semarang, 2025)
The community service activity conducted in Toapaya Selatan aimed to introduce an innovative planting and fertilizer applicator tool based on PVC pipes as an appropriate technology. This program was motivated by the persistence of manual farming practices that require excessive labor, time, and costs, while often resulting in uneven fertilizer distribution that reduces crop productivity. The implementation method adopted a participatory approach, consisting of preparation, counseling, demonstrations, field practice, and evaluation involving local farmers. Training sessions included hands-on practice to ensure that participants not only understood the theoretical aspects but also acquired practical skills in using and assembling the tool. The results indicate that the application of the pipe-based tool improved labor efficiency, reduced fertilization time, and enhanced the uniformity of fertilizer distribution on plantation land. These improvements were directly reflected in better crop maintenance and more sustainable use of resources. Farmers’ high enthusiasm and active participation demonstrated the success of this simple yet impactful technology transfer. Nevertheless, several challenges were encountered, including limited technical understanding among some participants, difficulties in replicating the tool independently, and restricted availability of tool-making materials in the local market. Overall, this innovation has the potential to contribute significantly to increasing local agricultural productivity. Further training, continuous mentoring, and institutional as well as financial support from the village government are strongly recommended to ensure the sustainability, scalability, and long-term adoption of this appropriate technology.